The Urgency of Enacting a Curator Profession Law to Ensure the Proper Exercise of Curators’ Functions and Powers - Muhammad Rayhan Fasya Akbar; Ridha Wahyuni (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The increasing prevalence of criminalization practices against curators in the performance of their duties and authorities indicates weaknesses in Indonesia’s bankruptcy law framework, particularly concerning the legal status of curators as a profession. Curators are often placed in a vulnerable position when carrying out statutory mandates, especially in the administration and liquidation of bankrupt estates, which may give rise to disputes with debtors or third parties. This research aims to analyze the legal position of curators as a profession within Indonesian bankruptcy law and to formulate an ideal legal framework to provide legal protection for the execution of curators’ duties and functions. The research employs a normative legal research method using statutory, conceptual, and comparative approaches, specifically by comparing the regulatory regime governing the curator profession in New Zealand under the Insolvency Practitioners Regulation Act 2019. The findings indicate that the current regulation of curators in Indonesia remains fragmented and fails to provide adequate legal certainty, thereby creating opportunities for criminalization and disparities in law enforcement. Therefore, this study concludes that the enactment of a specific law governing the curator profession as lex specialis is an urgent necessity to affirm the professional status of curators, strengthen oversight and accountability mechanisms, and provide proportional legal protection so that curators may perform their duties independently, professionally, and in good faith.